Monoarticular Hip Involvement in Pseudogout - Figen Kocyigit; Ersin Kuyucu; Ali Kocyigit (Case Reports in Rheumatology)
Pseudogout is the acutest form of arthritis in the elderly. Although clinical manifestations vary widely, polyarticular involvement is typical mimicking osteoarthritis or rheumatoid arthritis. Monoarticular involvement is relatively rare and is generally provoked by another medical condition. There are reported cases of hip involvement by pseudogout in monoarticular form. However, all of the cases were presented as septic arthritis. In this report, we present a case of monoarticular hip involvement mimicking soft tissue abscess. We confirmed the pseudogout diagnosis after ultrasonographic evaluation of the involved hip joint and pathological and biochemical analysis of synovial fluid analysis. Diagnosis is important to avoid unnecessary medical and surgical treatment in cases of the bizarre involvement of hip in pseudogout.